Pin it, tack it, hang it : the big book of kids' bulletin boards - Fiarotta, Phyllis (Workman Pub. Co., 1975)
Step-by-step instructions for constructing bulletin boards from different materials with suggestions for using them either as an activity center or a standing scrapbook reflecting the user's experiences or interests.